BINDER: An Extrusion-based Break-In Detector for Personal Computers - Cui, Weidong; Katz, Randy H.; Tan, Wai-tian (Proceedings of the 2005 USENIX Annual Technical Conference, 2005)
Compromised computers have been a menace to both personal and business computing. In this paper, we tackle the problem of automated detection of break-ins of new unknown threats such as worms, spyware and adware on personal computers. We propose Break-IN DEtectoR (BINDER), a host-based break-in detection system. Our key observation is that many break-ins make extrusions, stealthy malicious outgoing network connections. BINDER exploits a unique characteristic of personal computers, that most network activities are directly or indirectly triggered by user input. Since threats tend to run as background precesses and thus do not receive any user input, the intuition behind BINDER is that only threats generate connections without user input. By correlating outgoing network connections and processing information with user activities, BINDER can capture extrusions and thus break-ins.